2008
DOI: 10.1186/1751-0147-50-46
|View full text |Cite
|
Sign up to set email alerts
|

A review of the off-label use of selamectin (Stronghold®/Revolution®) in dogs and cats

Abstract: Since its introduction approximately seven years ago, selamectin (Stronghold®/Revolution®, Pfizer Inc.) has been used off-label to treat a number of ecto- and endoparasite conditions in dogs and cats. It has been used as a successful prophylactic against Dirofilaria repens and as a treatment for Aelurostrongylus abstrusus in cats. It has also been used to treat notoedric mange, infestation with the nasal mite Pneumonyssoides caninum, Cheyletiella spp. and Neotrombicula autumnalis infestations and larval Cordyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…abstrusus and C . aerophila in clinical trials, given the scant reports published thus far [188-190]. The recent reports of the efficacy of the spot-on formulation containing moxidectin in the treatment of feline aelurostrongylosis and capillariosis [169,191] should encourage further studies aiming to also investigate the applicability of chemopreventative approaches against these parasites, as recently assessed for dog angiostrongylosis [136].…”
Section: Resultsmentioning
confidence: 99%
“…abstrusus and C . aerophila in clinical trials, given the scant reports published thus far [188-190]. The recent reports of the efficacy of the spot-on formulation containing moxidectin in the treatment of feline aelurostrongylosis and capillariosis [169,191] should encourage further studies aiming to also investigate the applicability of chemopreventative approaches against these parasites, as recently assessed for dog angiostrongylosis [136].…”
Section: Resultsmentioning
confidence: 99%
“…In the few reports investigating activity against harvest mites, none had a control group [12,13,22]. We elected to include a control group to ensure that the reduction of the lesions in dogs receiving the treatment was not spontaneous and avoid misinterpretation of the results as trombiculiosis is a seasonal skin disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, it was found to be a highly effective and broad-spectrum drug that was safe for animals (including rhesus macaques, dogs, cats, rats, rabbits, and ferrets; Esatgil et al 2008;Fisher and Shanks 2008;Kim et al 2008;Miller et al 2006;Wang et al 2008a).…”
Section: Discussionmentioning
confidence: 99%